Practice follows structure: QM in Malaysian public hospitals - Abd. Manaf, Noor Hazilah (Emerald Group Publishing Limited, 2009)
Purpose – The main aim of this study is to provide an empirical analysis on the practice of quality management among employees of Malaysian public hospitals at the district, state and national level hospitals. This paper aims to perform a comparative analysis on quality management practices among the three levels of hospitals.